(untitled) (Journal of Bio-Science, 2019)
The aqueous fruit extracts of the pepper Capsicum annuum L. (Solanales: Solanceae) were tested against the four larval stages of the tomato leafminer (TLM) Tuta absoluta Povolny (Lepidoptera: Gelechiidae). Random samplings were made from two greenhouses of Biskra, in the Southeast of Algeria. About 750 to 800 plants of the Sahara variety of tomatoes were planted in both greenhouses. In the laboratory, conditions with temperature, relative humidity (RH) and the photoperiod were 25° to 30°C, from 50% to 60% and 16L: 8D, respectively. A breeding of our species in the laboratory was made during six months of the study. For the toxicological assessments, three concentrations were chosen; 50 mg/L, 100 mg/L and 200 mg/L of the extracts. The results revealed that the extracts of C. annuum were very effective against the larvae of T. absoluta. After 24 h post-treatment, the mortality was less than 25% compared to that after 48h and 72h post-treatment which exceeded 50%. There was a non-significant difference in mortality rates between the four larval stages (F3, 140 = 1.12; P = 0.344). In contrast, highly significant differences existed between the time of exposure (F2, 141 = 26.2; P = 0.001) and the concentrations under study (F3, 140 = 59.6; P = 0.001). J. bio-sci. 26: 25-30, 2018